School Leaders as Participants in Teachers’ Professional Development: The Impact on Teachers’ and School Leaders’ Professional Growth - Hilton, Annette; Hilton, Geoff; Dole, Shelley; Goos, Merrilyn (Australian Journal of Teacher Education, 2015)
Over a two-year period, approximately 70 teachers from 18 schools participated in an on-going professional development program as part of a study to promote the teaching and learning of numeracy. Principals and other school leaders were invited to participate in the professional development program alongside their teachers, which 20 leaders from 11 schools chose to do. Throughout the project, data were collected from teachers and participating school leaders using surveys, interviews, and workshop discussions to investigate teachers’ and leaders’ professional growth. The findings showed that school leaders’ participation in teacher professional development programs has a positive influence on the capacity for teachers to enact and reflect on new knowledge and practices. They also revealed a positive influence on the professional growth of the leaders themselves. This study has implications for the design of professional development and for school leaders and teacher educators.